Biosilica aging: From enzyme-driven gelation via syneresis to chemical/biochemical hardening - Wang, Xiaohong; Schröder, Heinz C.; Schloßmacher, Ute; Jiang, Lei; Korzhev, Michael; Müller, Werner E.G. (Biochimica et biophysica acta, 2013)
The distinguished property of the siliceous sponge spicules is their enzyme (silicatein)-catalyzed biosilica formation. The enzymatically formed, non-structured biosilica product undergoes a molding, syneresis, and hardening process to form the species-specifically shaped, hard structured skeletal spicules. Besides of silicatein, a silicatein-associated protein, silintaphin-2, is assumed to be involved in the process of biosilica formation in vivo. Biosilica has been synthesized enzymatically and determined quantitatively. In addition, the subsequent hardening/aging steps have been followed by spectroscopic and electron microscopic analyses. The young spicules, newly formed in sponge cell aggregates, comprise high concentrations of sodium (~1w/w%) and potassium (0.3%). During aging the two alkali metals are removed from the spicules by 80%. In parallel, water is withdrawn from the biosilica deposits. A protein, the silicatein-α interactor silintaphin-2, comprises clusters rich in the anionic amino acids aspartic acid [D] and glutamic acid [E]. The very acidic peptide was found to significantly enhance silica polymerization. This peptide also caused a strong aggregation of silicatein/biosilica particles. The observations are explained by sodium ion removal from the initially formed biosilica deposits to the acidic amino acids in silintaphin-2. The crucial amino acids facilitating/forcing the silicatein-mediated biosilica reaction are D and E. The data presented here provide a reaction mechanism that at neutral pH the extent of biosilica formation can be strongly intensified by the removal of cations. The results contribute to an understanding of the structuring process taking place during the formation of the solid spicule rods. [Display omitted] ► Sponge skeleton/biosilica is synthesized by silicatein at physiological conditions. ► During aging of biosilica alkali metal ions are removed from biosilica. ► Silicatein-associated protein silintaphin-2 accepts the metal ions. ► Presence of silintaphin-2 intensifies silicatein-mediated biosilica formation. ► Reaction mechanism presented explains the structuring process of biosilica.